Role of glycogen synthase kinase 3 (GSK-3) and its substrate proteins in the development of cardiomyopathy associated with obesity and insulin resistance - Flepisi, Thabile Brian (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MScMedSc)--University of Stellenbosch, 2011.